Neonatal Status Epilepticus Secondary to Nonketotic Hyperglycinemia: Efficacy of Low-Dose Dextromethorphan - Vila-Bedmar, Sara; La-Vega Talbott, Maite (Journal of Pediatric Epilepsy, 2023)
Nonketotic hyperglycinemia is a severe form of early onset epileptic encephalopathy caused by disturbances in the glycine cleavage system, leading to neurological damage attributed to overstimulation of the N-methyl-D-aspartate receptor. Although there are no interventions known to be effective in altering the natural history of nonketotic hyperglycinemia, it is very important that the clinician recognizes this disease and initiates early evaluation and treatment to attain the best possible outcome. Here we present a newborn diagnosed with a severe form of nonketotic hyperglycinemia with frequent myoclonic seizures, which were resistant to phenobarbital, levetiracetam, ketogenic diet, sodium benzoate, and perampanel. Dextromethorphan reduced epileptic myoclonic jerks and improved the background activity on the electroencephalogram.
Keywords: neonatal status epilepticus; EEG; nonketotic hyperglycinemia; dextromethorphan